2020
DOI: 10.1371/journal.pbio.3001025
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome landscape of ovarian cells during primordial follicle assembly in mice

Abstract: Primordial follicle assembly in the mouse occurs during perinatal ages and largely determines the ovarian reserve that will be available to support the reproductive life span. The development of primordial follicles is controlled by a complex network of interactions between oocytes and ovarian somatic cells that remain poorly understood. In the present research, using single-cell RNA sequencing performed over a time series on murine ovaries, coupled with several bioinformatics analyses, the complete dynamic ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 89 publications
3
85
0
Order By: Relevance
“…Deleting both factors in mice caused defects in both oocyte and granulosa cells during primordial follicle assembly (Fu et al, 2018). These results show that communication between all the cells involved is essential for proper germ cell cluster breakdown and PF assembly (Fu et al, 2018;Wang et al, 2020).…”
Section: Ovarian Follicle Assemblymentioning
confidence: 93%
“…Deleting both factors in mice caused defects in both oocyte and granulosa cells during primordial follicle assembly (Fu et al, 2018). These results show that communication between all the cells involved is essential for proper germ cell cluster breakdown and PF assembly (Fu et al, 2018;Wang et al, 2020).…”
Section: Ovarian Follicle Assemblymentioning
confidence: 93%
“…Using single-cell sequencing, individual cells are clustered together into related populations based on transcriptomic data. In the ovary, the pregranulosa cell lineages and subclusters have been reconstructed using single-cell data sets (Niu and Spradling 2020;Wang et al 2020). Comprehensive data sets covering the stages of germ cell nest breakdown, primordial follicle formation, and primordial follicle activation were generated using single-cell sequencing on whole ovaries from E18.5, PND1, and PND5 (Niu and Spradling 2020).…”
Section: Germ Cell Nest Breakdown Leads To the Formation Of Primordial Folliclesmentioning
confidence: 99%
“…Importantly, in the Niu and Spradling (2020) data set, all three Cip/Kip family members Cdkn1a, Cdkn1b, and Cdkn1c are all expressed in both pregranulosa populations, whether the cells are of a bipotential cell origin or an epithelial cell origin. A subsequent study from Wang et al (2020) performed a similar study at E16.5, PND0, and PND3 to better understand the dynamics of primordial follicle assembly. This study confirmed the presence of multiple populations of pregranulosa cells and went one step further to examine the transcriptional networks that are involved in the interactions between oocytes and pregranulosa cells (Wang et al 2020).…”
Section: Germ Cell Nest Breakdown Leads To the Formation Of Primordial Folliclesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ) ( Fu et al , 2018 ; Lv et al , 2019 ; Stevant and Nef, 2019 ). To support these numerous developmental pathways, there is heterogeneity within the granulosa cell population ( Rastetter et al , 2014 ; Niu and Spradling, 2020 ; Wang et al , 2020 ). For example, two populations of primordial follicles are formed within the ovary, distinguished by their location in the ovary and the expression of either Forkhead box L2 (FOXL2) or Leucine Rich Repeat Containing G Protein-Coupled Receptor 5 (LGR5) in the granulosa cells ( Rastetter et al , 2014 ; Niu and Spradling, 2020 ).…”
Section: Introductionmentioning
confidence: 99%